The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1128/jvi.01070-17
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Exposed Infants Vaccinated with an MF59/Recombinant gp120 Vaccine Have Higher-Magnitude Anti-V1V2 IgG Responses than Adults Immunized with the Same Vaccine

Abstract: In the RV144 vaccine trial, IgG responses against the HIV envelope variable loops 1 and 2 (V1V2) were associated with decreased HIV acquisition risk. We previously reported that infants immunized with an MF59-adjuvanted rgp120 vaccine developed higher-magnitude anti-V1V2 IgG responses than adult RV144 vaccinees. To determine whether the robust antibody response in infants is due to differences in vaccine regimens or to inherent differences between the adult and infant immune systems, we compared Env-specific I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Our data from the Env-only vaccine regimen are consistent with the induction of persistent Env-specific antibody responses in human infants (10). It should be emphasized again that HIV Env-specific V1V2 IgG responses were induced at a higher magnitude in human infants than in adults (11). Similarly, the hepatitis B vaccine and the human papillomavirus vaccine are known to induce stronger antibody responses in infants than in adults (32,33).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data from the Env-only vaccine regimen are consistent with the induction of persistent Env-specific antibody responses in human infants (10). It should be emphasized again that HIV Env-specific V1V2 IgG responses were induced at a higher magnitude in human infants than in adults (11). Similarly, the hepatitis B vaccine and the human papillomavirus vaccine are known to induce stronger antibody responses in infants than in adults (32,33).…”
Section: Discussionsupporting
confidence: 82%
“…Highly relevant to the studies here, the retrospective analysis of plasma samples from early HIV Env vaccine trials in human infants demonstrated that vaccination of neonates with HIV Env elicited persistent Env-specific plasma IgG antibodies (10). Furthermore, antibody responses were not only durable for up to 2 years, but the magnitude of plasma IgG antibodies specific to the V1V2 region exceeded those of adults in the RV144 trial (10,11).…”
Section: Importancementioning
confidence: 59%
“…Our results suggest that the humoral immune response to SHIV infection develops similarly in adult and infant RMs and corroborate findings in human cohorts demonstrating that infants can develop robust HIV Env binding and neutralizing antibody responses despite their maturing immune landscape. Additionally, we have demonstrated that the Tfh landscape during acute infection in infants is distinct from that in adults, which may offer a potential advantage for infant vaccination, especially since studies suggest that infants are able to mount robust antibody responses to HIV Env vaccination, and these responses tend to be comparable or superior to those of adults (55)(56)(57)(58). However, gaps in our knowledge still exist when it comes to understanding the infant immune response to HIV infection and how it can be harnessed for optimal vaccine-mediated protection against HIV-1.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that infants can elicit immune responses of greater breadth compared to adults and develop higher magnitude antibody responses to some protein vaccine antigens like Human Papillomavirus Virus-Like-Particle, HIV, and Hepatitis B. [65][66][67][68][69] Investigating the diversity and potency of pediatric antibody responses may help to define immune correlates of protection against COVID-19 and cross-protective epitopes on S to guide long-term CoV vaccine strategies. candidates expressing viral proteins and immunomodulatory genes (Shenzhen Geno-Immune Medical Institute; Trial IDs: NCT04299724 and NCT04276896).…”
Section: For Example Virus-specific Cd8+ T Cells Play An Important Rmentioning
confidence: 99%